Meningkatkan Kemampuan Berhitung Melalui Media Kartu Angka Interaktif Pada Kelompok Usia 5-6 Tahun Taman Kanak – Kanak Taman Hijau, Kota Batam - Diana Indah Palupi; Diana Earlyana Lesmana; Dian Farista; Emma Rahmani; Erlin Yusnita; Agus Sudarya (Publikasi Indonesia, 2022)
Children begin to enter the preschool period in the age range of 5-6 years, this age is a period of preparation to enter formal education actually in elementary school. Cognitive development is one aspect of development that must always be given stimulation. The ability to count is part of the aspect of cognitive development. The purpose of this study in general is